Del bipartidismo a la pluralidad política en la Comunidad de Madrid: cambios territoriales (2011-2019) - Fernández Portela, Julio; Martín Roda, Eva María; Muguruza Cañas, María del Carmen; Vidal Domínguez, María Jesús (Geographicalia, 2020)
Our current political situation is characterized by a fragmented vote that has led to the weakening and, in some territories, the end of bipartisanship, as is the case of the Community of Madrid (CM). The PP and the PSOE’s majority governments have given way to more diverse governments, where negotiating and reaching agreements has become indispensable. This paper analyses the reorganization and the political map’s current situation, which has gone from being monochromatic to polychromatic in just eight years, with notable territorial differences. To do so, the 2011, 2015 and 2019 municipal electoral results held will be studied For this study, data provided by the Ministry of Interior and the Community of Madrid, as well as the Register of the National Statistics Institute.